Analysis on Circulating Current Loss in the Formed Winding of Permanent Magnet Synchronous Motors - Jia Liu; Yanping Liang; Peipei Yang; Weihao Wang; Fuchao Zhao; Kangwen Xu (IEEE Access, 2021)
Permanent magnet synchronous motors with the formed winding can not only improve the slot fill factor and heat dissipation capacity but also effectively reduce the additional loss in the winding. Formed winding permanent magnet synchronous motors will become the future development tendency. Due to inherent features of the formed winding, the circulating current loss is a non-negligible issue. This paper proposes using the formed winding in permanent magnet synchronous motors and analyzes the circulating current loss in the formed winding. First, the finite element models of integer slot and fractional slot motors are established, and the magnetic field analysis are carried out. Then two commonly used methods of calculating circulating current loss are introduced in detail, and their calculation results are compared. Moreover, the high-precision field-circuit coupled finite element method is used to calculate the circulating current loss of integer and fractional motors. And circulating currents of the hairpin winding and the formed winding are compared. The analysis indicates that the circulating current in the formed winding cannot be ignored. Finally, comprehensive and in-depth research on the influencing factors of circulating current loss in the formed winding has been conducted. The results clarify that the number of parallel strands, the width of the slot opening, and the stator current have a considerable influence on the circulating current loss.